Graphic Communication in Science - A Guide to Format, Techniques, and Tools - Guidry, Nelson P.; Frye, Kenneth B.; National Science Teachers Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
This booklet on graphical techniques of communications in science was written to aid the student who might be engaged in a project in which a quality report will be required. Written for the secondary school student, it concentrates on the graphic presentation of data, indicating the planning and techniques involved as well as the supplies and instruments that are generally used. Topics include (1) nature of graphic presentations, (2) choosing a graphic form, (3) the professional touch, (4) tools of the trade, (5) charts, and (6) maps. Section II deals with tools and specific techniques. A bibliography is included. (DH)
Availability: NEA Publications Sales, 1201 16th Street, N.W., Washington, D.C. 20036 ($2.00).
Microfiche.
Keywords: Bibliographies; Communication Skills; Engineering Graphics; Graphic Arts; Instructional Materials; Secondary School Science; Technical Writing